2005
DOI: 10.1093/hmg/ddi465
|View full text |Cite
|
Sign up to set email alerts
|

β-Mannosidosis mice: a model for the human lysosomal storage disease

Abstract: Beta-mannosidase, a lysosomal enzyme which acts exclusively at the last step of oligosaccharide catabolism in glycoprotein degradation, functions to cleave the unique beta-linked mannose sugar found in all N-linked oligosaccharides of glycoproteins. Deficiency of this enzyme results in beta-mannosidosis, a lysosomal storage disease characterized by the cellular accumulation of small oligosaccharides. In human beta-mannosidosis, the clinical presentation is variable and can be mild, even when caused by function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
2
27
0
1
Order By: Relevance
“…Using the protein atlas 59 and Illumina Body Map (GEO: GSE30611), we found that the reproductive tract and the kidney both have intermediate expression of MANBA (not shown), and MANBA is expressed in lysosome of kidney tubule cells ( Figure 4A). 60 Segment-specific expression data obtained from rat kidneys 61 indicate that Manba is expressed in the loop of Henle, with the highest expression level in medullary collecting duct segment.…”
Section: Analysis Of Manba Gene Expressionmentioning
confidence: 99%
“…Using the protein atlas 59 and Illumina Body Map (GEO: GSE30611), we found that the reproductive tract and the kidney both have intermediate expression of MANBA (not shown), and MANBA is expressed in lysosome of kidney tubule cells ( Figure 4A). 60 Segment-specific expression data obtained from rat kidneys 61 indicate that Manba is expressed in the loop of Henle, with the highest expression level in medullary collecting duct segment.…”
Section: Analysis Of Manba Gene Expressionmentioning
confidence: 99%
“…This has in part been attributed to the fact that b-mannosidosis deficient ruminants accumulate the trisaccharide Man(b1-4) GlcNAc (b1-4) GlcNAc to a greater extent than the disaccharide Man(b1-4) GlcNAc (Jones et al 1992). However humans who, like other nonruminants, have an additional lysosomal enzyme chitobiase (Zhu et al 2006) accumulate the disaccharide (Cooper et al 1988). This potential correlation between phenotype and predominating oligosaccharide is strengthened by the fact that the mouse model, where predominately disaccharides accumulate, also exhibits a mild phenotype with no obvious dysostosis (Zhu et al 2006).…”
Section: Case Reportmentioning
confidence: 99%
“…However humans who, like other nonruminants, have an additional lysosomal enzyme chitobiase (Zhu et al 2006) accumulate the disaccharide (Cooper et al 1988). This potential correlation between phenotype and predominating oligosaccharide is strengthened by the fact that the mouse model, where predominately disaccharides accumulate, also exhibits a mild phenotype with no obvious dysostosis (Zhu et al 2006).…”
Section: Case Reportmentioning
confidence: 99%
“…A mouse model of b-mannosidosis was created by targeted disruption of the b-mannosidase gene by homologous recombination in 129X1/SvJ ES cells (Zhu et al 2006). Homozygous mutant animals had the expected enzyme deficiency and had accumulation of disaccharide in brain tissue, but showed normal growth, appearance, and lifespan.…”
mentioning
confidence: 99%
“…Previous examination of mutant animals between 1 and 9 months of age showed selective, variable neuronal vacuolation with no hypomyelination, closer to what would be expected in the human b-mannosidosis phenotype given the human clinical presentation. Cell populations identified with variable vacuolation included pyramidal cells (layer V) in dorsolateral cortex, choroid plexus, specific segments of Ammon's horn, striatum, amygdala, deep cerebellar nuclei, and spinal cord (Zhu et al 2006).…”
mentioning
confidence: 99%